2010
DOI: 10.4028/www.scientific.net/amr.123-125.1231
|View full text |Cite
|
Sign up to set email alerts
|

Fibre-Fibre Hybrid Composites for Aerospace Applications

Abstract: The extruded poly ether ether ketone (PEEK) and glass fibre were used to obtain the co-woven hybrid fibre fabrics and converted into composites using compression moulding technique. The effect of shear stress and shear rate on the shear viscosity of PEEK was investigated to optimise the process conditions for converting hybrid fabrics into composites. The mechanical properties such as flexural strength and inter laminar shear strength (ILSS) as a function of number of layers of fabric have been evaluated. Low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…It can be seen that the measured values in the case of bidirectional laminates (Table 8) irrespective of annealing conditions and weave are significantly less compared to unidirectional composites (Table 7; all the glass fibers aligned in one direction). The measured values reported for glass-epoxy systems with similar resin content, and thickness indicates that ILSS, flexural, and tensile strength values of glass-PEEK composites achieved in this case are significantly high to an extent of 30-40% [35,36].…”
Section: Effect Of Weave Lay-up and Annealing Conditionsmentioning
confidence: 95%
See 2 more Smart Citations
“…It can be seen that the measured values in the case of bidirectional laminates (Table 8) irrespective of annealing conditions and weave are significantly less compared to unidirectional composites (Table 7; all the glass fibers aligned in one direction). The measured values reported for glass-epoxy systems with similar resin content, and thickness indicates that ILSS, flexural, and tensile strength values of glass-PEEK composites achieved in this case are significantly high to an extent of 30-40% [35,36].…”
Section: Effect Of Weave Lay-up and Annealing Conditionsmentioning
confidence: 95%
“…Special mention about the ductile behavior of PEEK should be made as its role in enhancing the overall ductile behavior or reducing the brittle nature of glass-PEEK composites is primarily responsible for the superior mechanical and impact properties. The effects of annealing on mechanical behavior are worth mentioning because they lead to changes in the aspect of the tensile curves that might be a sign of rearrangements occurring on PEEK crystalline structure [34]. Tables 7 and 8 show the mechanical properties of unidirectional (glass fiber in the longitudinal direction) and bidirectional (every alternate layers of glass in longitudinal and lateral directions) glass-PEEK composites processed at long processing cycle (210 minutes), respectively.…”
Section: Effect Of Weave Lay-up and Annealing Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Investigations of Xu et al 6 revealed that the composites fabricated using the concept of hybridization of glass, polypropylene, and polyvinyl alcohol (PVA) fibers have offered more attractive engineering properties than the composites made with only one type of fiber. The excellent drapability and flexibility of hybrid yarn fabrics 7,8 can be utilized to fabricate certain complex shape for radome applications. Radome (is the word stands for radar and dome) is a structural, weatherproof enclosure that protects a microwave or radar antenna.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to their high temperature thermal stability, continuous use temperature, solvent resistance (lack of solubility in common solvents), mechanical strength, elastic modulus, high toughness, wear resistance, reprocessability, and techno-commercial advantages over conventional thermoset based systems. [7][8][9][10] The nature of fiber-fiber interface in thermoplastic composites and process optimization offers most challenging aspects to be studied.…”
Section: Introductionmentioning
confidence: 99%